The future of regional development and public investment in Wales, United Kingdom - Organisation for Economic Co-operation and Development (OECD multi-level governance studies, ISSN 2414-6781, 2020)
Summary.
Keywords: hallinto : Iso-Britannia; aluehallinto : Wales; aluekehitys : Wales; investoinnit : Wales; suorat investoinnit : Wales